General Self-Efficacy and Employability Among Financially Underprivileged Chinese College Students: The Mediating Role of Achievement Motivation and Career Aspirations - Wang, Dan; Guo, Danyang; Song, Chao; Hao, Lianming; Qiao, Zhihong (Frontiers in Psychology, 2022)
Although current research indicates that general self-efficacy is related to employability, the mechanisms by which general self-efficacy affects employability are unclear. We thus explored the relationship between general self-efficacy and employability and examined the mediating role of achievement motivation and career aspirations among financially underprivileged college students in China. We included 651 participants (59% female, 41% male) from 6 provinces. Results showed that general self-efficacy positively predicted employability through the mediating role of achievement motivation. Career aspirations mediated the relationship between general self-efficacy and employability. Achievement motivation and career aspirations mediated the link between general self-efficacy and employability. Our finding selucidate the effects of general self-efficacy, achievement motivation, and career efficacy on employability and their mechanisms of action, which has implications for maintaining and promoting the employability of financially underprivileged college students.